Exploring stevioside binding affinity with various proteins and receptors actively involved in the signaling pathway and a future candidate for diabetic patients - Khan, Salman; Ahmad, Nisar; Fazal, Hina; Saleh, Ibrahim A.; Abdel-Maksoud, Mostafa A.; Malik, Abdul; AbdElgayed, Gehad; Jalal, Arshad [UNESP]; Rauf, Kamran; Ali, Liaqat; Ullah, Sami; Niqabullah,; et al. (Frontiers, 2024)
Introduction and Background: Diabetes is a chronic metabolic disease characterized by elevated blood glucose levels and is one of the main global health concerns. Synthetic sugar substrate has many side effects such as leukemia, bladder cancer, hepatotoxicity, breast cancer, headache, and brain toxicity. The WHO and FDA has recently banned some of the synthetic sugar alternatives due to their carcinogenic effects. Objective and Methodology: Therefore, the main objective of the current study was to investigate the safety and binding affinity of Stevioside with Glucose Transpoter-4 (GLUT-4), Akt, Insulin Receptor (IR) and Insulin Receptor Substrate-1 (IRS-1) to confirmed that Stevioside is one the potent natural sweetener/drug for diabetes. This study delves into the molecular interaction between Stevioside and key diabetic proteins: GLUT-4, Akt, IR and IRS-1. A precise molecular docking approach was used to simulate the binding affinity of Stevioside to these proteins. The pharmacokinetic properties of the molecule should be taken into consideration as important variables throughout the virtual screening process. Results: The result of active site analysis of GLUT-4, Akt, IR and IRS-1 showed a zone of 2158.359 Ǻ2, 579.259 Ǻ2, 762.651 Ǻ2, and 152.167 Ǻ2 and a volume of 2765.094 Ǻ³, 355.567 Ǻ³, 686.806 Ǻ³, and 116.874 Ǻ³, respectively. Docking analysis of the Stevioside compound showed the highest docking energy with scores of −9.9 with GLUT-4, −6.7 with Akt, −8.0 with IR and −8.8 with IRS-1. Studies indicated that it remains undigested by stomach acids and enzymes and is not absorbed in the upper small intestine. Further, tests revealed no hepatotoxicity, AMES toxicity, or skin sensitivity, making it a promising candidate for safe consumption as drug metabolism. Conclusion and Recommendations: Instead of other sugar alternatives, Stevioside will help diabetic patients with a lower chance of infections, lowered blood pressure/blood sugar, and increased glucose uptake in diabetic muscles. Stevioside is a natural sweetener, and the current study recommends its usage in various dietary products for diabetic patients.
Keywords: Akt; diabetes; insulin receptor substrate; molecular docking; safe drug; stevioside; sugar alternative